If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying (x + 11)(x + -4) = 34 Reorder the terms: (11 + x)(x + -4) = 34 Reorder the terms: (11 + x)(-4 + x) = 34 Multiply (11 + x) * (-4 + x) (11(-4 + x) + x(-4 + x)) = 34 ((-4 * 11 + x * 11) + x(-4 + x)) = 34 ((-44 + 11x) + x(-4 + x)) = 34 (-44 + 11x + (-4 * x + x * x)) = 34 (-44 + 11x + (-4x + x2)) = 34 Combine like terms: 11x + -4x = 7x (-44 + 7x + x2) = 34 Solving -44 + 7x + x2 = 34 Solving for variable 'x'. Reorder the terms: -44 + -34 + 7x + x2 = 34 + -34 Combine like terms: -44 + -34 = -78 -78 + 7x + x2 = 34 + -34 Combine like terms: 34 + -34 = 0 -78 + 7x + x2 = 0 Factor a trinomial. (-13 + -1x)(6 + -1x) = 0Subproblem 1
Set the factor '(-13 + -1x)' equal to zero and attempt to solve: Simplifying -13 + -1x = 0 Solving -13 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '13' to each side of the equation. -13 + 13 + -1x = 0 + 13 Combine like terms: -13 + 13 = 0 0 + -1x = 0 + 13 -1x = 0 + 13 Combine like terms: 0 + 13 = 13 -1x = 13 Divide each side by '-1'. x = -13 Simplifying x = -13Subproblem 2
Set the factor '(6 + -1x)' equal to zero and attempt to solve: Simplifying 6 + -1x = 0 Solving 6 + -1x = 0 Move all terms containing x to the left, all other terms to the right. Add '-6' to each side of the equation. 6 + -6 + -1x = 0 + -6 Combine like terms: 6 + -6 = 0 0 + -1x = 0 + -6 -1x = 0 + -6 Combine like terms: 0 + -6 = -6 -1x = -6 Divide each side by '-1'. x = 6 Simplifying x = 6Solution
x = {-13, 6}
| 72=6r | | X^2-6x+84=0 | | 9+6x-5=7x+10-4x | | (7a^3b^-4/2a^-2b)^-2 | | 4x^2-1x-9=y | | x^2+10x=-40 | | 12x+31y=170 | | 2(v+7)=-3v-1 | | (-7c+2)(2c+3)=0 | | (2-3i)(7-6i)=0 | | 2v+11=9(v+9) | | -4x^2+56x-296=0 | | 4/7z=12/35 | | 5(4b-4)=-60 | | -24=3(y-2)-5y | | -3+4=16 | | 4(2m+6)+3(3m+7)= | | 3+4x+10=-5 | | 2(d+1)-3=9 | | 5x+7y+(-7y)+(-8x)= | | 0.08x=-48 | | 5(v+2)-2v=1 | | u^4+u^2v^2-5u^2-5v^2=0 | | -15=6(w-7)-3w | | x-7=6x-2 | | x+x+6=18 | | 3/4(4) | | -5y+2=2(4-y) | | -6u+2(u+6)=-24 | | 5x^2-37xy+14y^2=0 | | 3/4(4x-8) | | s^2+s=72 |